Simulação de Monte Carlo no modelo de Ising na rede quadrada - Murilo Lacerda Santos (2014)
In this work we study the magnetic properties of the ferromagnetic Ising model on a square lattice, in zero external magnetic eld, through Monte Carlo simulations. The initial part comprises the theoretical background and the simulations as the Monte Carlo code, the single histogram technique and the estimate of the error bars. For the particular four-spin cluster the exact results have been obtained and compared to the simulational ones. Such comparison granted a better understanding of the process of generating the computational data besides a way of conrming the correctness of the code. Together with the single histogram technique and the nite size scaling hypothesis. We have obtained the mean values of the magnetization, energy, specic heat, susceptibility and the Binder cumulant. It was possible to obtain the thermodynamic quantities as a function of temperature and the system size. It was evident the existence of a phase transition with its peculiar behavior. Accordingly, we have obtained the critical temperature as well as the critical exponents of the model. The values of the critical indices and the critical temperature agree well with the exact ones and those coming from other computational methods.